2016
DOI: 10.1002/bjs.10222
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of same-admission versus interval cholecystectomy after mild gallstone pancreatitis in the PONCHO trial

Abstract: In mild biliary pancreatitis, same-admission cholecystectomy was more effective and less costly than interval cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 27 publications
0
27
0
6
Order By: Relevance
“…Figure 1 shows the modified PRISMA flowchart for identification and inclusion of relevant papers. Twentythree studies were excluded from the meta-analysis; 10 papers were deemed low quality [53][54][55][56][57][58][59][60][61] and 13 papers did not provide readmission rates specific to LC [62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the modified PRISMA flowchart for identification and inclusion of relevant papers. Twentythree studies were excluded from the meta-analysis; 10 papers were deemed low quality [53][54][55][56][57][58][59][60][61] and 13 papers did not provide readmission rates specific to LC [62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Resultsmentioning
confidence: 99%
“…However, da Costa and colleagues 29 have established the cost-effectiveness of their included RCT 24 . This demonstrated that EC was more cost-effective, with a mean total saving of €234 per patient 29 . Furthermore, Morris et al 30 demonstrated that laparoscopic cholecystectomy within 3 days of admission saves €795, with a 0⋅004 increment in quality-adjusted life-years.…”
Section: Discussionmentioning
confidence: 99%
“…8900, which is comparable with Da costa et al study. 16 In interval group readmission rate of 19% with no readmission in same admission group, comparable with International Surgery Journal | January 2020 | Vol 7 | Issue 1 Page 256 same admission cholecystectomy for mild gallstone pancreatitis has significant advantage of reducing recurrent gallstone pancreatitis. 17,18 The mean intra operative time in same admission group is 85min versus 92 min in interval group is comparable with Shir le jee et al 15 There was no conversion to open cholecystectomy in same admission group but in interval group 6.4% (2) had conversion to open surgery, because of dense adhesion and frozen calot's, due to which dissection was difficult, comparable with Johnstone et al 19 In both the groups there was no intraoperative and postoperative complication and is comparable with Aboulian et al 20 Data from the above study and also from other studies, it is found that the ideal timing for mild gallstone pancreatitis is same admission laparoscopic cholecystectomy over interval cholecystectomy by reducing the cost and duration of hospital stay, readmission due to recurrent pancreatitis.…”
Section: Discussionmentioning
confidence: 55%